PELAKSANAAN KERJA SAMA BISNIS PADA USAHA DAGANG (UD) YUSUF BANGUNAN BATUSANGKAR - Yunimar Yunimar (IAIN Batusangkar, 2015)
This study was purposed at describing the implementation of business cooperation UD. Yusuf; describing the conflicts were arisen from business cooperation at UD. Yusuf and describing the fiqh muamalah perspective for the resolution of UD. Yusuf. This study was called non-doctrinal research. Interview and documentation were used as instruments in this study. The qualitative data analysis was done this study by applying data reduction; data display; and conclusion drawing/verification. The findings concluded that the business cooperation UD. Yusuf was not based syariah, it was based on trust. The conflict on business cooperation UD. Yusuf should be overcome in Shulh, Tahkim, Wilayat Al Hisbah, or Al Qadha. Based on the fiqh muamalah perspective, it should be solved based on Al-Baqarah 282.Keywords: The Implementation of Business Cooperation, Conflicts, Fiqh muamalah